Do Dutch Musea Compete Or Cooperate? - Thomas De Graaff; Jaap Boter; Jan Rouwendal (European Regional Science Association (ERSA), 2006)
This paper looks into the effect of distance on market shares of Dutch museums. To this end, we assume a generic distance decay function for all museums. In addition, we allow for spatial dependence between museums to account for local competition or synergy effects. Using a unique transaction database with the visiting behavior of 80,821 museum cardholders to 108 Dutch museums, we are able to calculate market shares of each museum in all 484 Dutch municipalities. To account for possible measurement error in the market shares, we adopt a spatial two error component model. Finally, we allow for additional heterogeneity by segmenting the 108 museums using a mixture approach. Without segmenting, preliminary results indicate positive spatial dependence between museums, which points to the conclusion that – in general – museums benefit from each others presence.
Keywords: 330